Determination of soil-water characteristics curves of sands using the evaporation method - On, Roger Zhi Wei (Nanyang Technological University, 2024)
Commonly, the Soil-Water Characteristic Curves (SWCCs) of sands are determined using the suction table and the Tempe cell method. Lately, a commercial system (HYPROP 2) has been increasingly used to determine SWCCs and permeability function in the low suction range (0-200 kPa). The HYPROP 2 is based on the evaporation method. The HYPROP 2 uses two small tensiometers and a weighing balance to work out the soil-water characteristic curve and permeability function using a software to perform inverse analysis.